(untitled) (The Planet, 2025)
Dyspnea is a common symptom with whic h patient may present to doctor of any discipline of medical science. About 3.5% of people present to the emergency department in the United States with dyspnea. Among them, approximately 51% are admitted to the hospital and 13% die within a year [1]. Some studies have suggested that up to 27% of hospitalized patients develop dyspnea [2], while 75% will experience dyspnea at their departure [3]. Acute dyspnea is the most common reason for palliative care patients to visit an emergency department [4]. Up to 70% of adults with advanced cancer also experience dyspnea [5]. Dyspnea (in American English) or Dyspnoea (in British English) means shortness of breath (SOB). The American Thoracic Society defines dyspnea as a subjective experience of breathing discomfort that consists of qualitatively distinct sensations that vary in intensity [6]. Other definitions of dyspnoea include: - • awareness of respiratory distress • an uncomfortable sensation of breathing • difficult, laboured, uncomfortable breathing • the sensation of feeling breathlessness or experiencing air hunger. Dyspnea is a normal symptom of heavy physical exertion that is physiological and disappears after rest, but becomes pathological if it occurs in unexpected situations, when resting or during light exertion [7]. DiagnosisPro, an online medical expert system, listed 497 distinct causes of dyspnea in October 2010[8] . Cardiorespiratory causes such as asthma, chronic obstructive pulmonary disease, pneumonia, COVID-19, interstitial lung disease, cardiac ischemia, and congestive heart failure accounts for 85% cases of dyspnea [7,9]. The rest is due to other causes like psychogenic causes such as panic disorder and anxiety, obesity, pregnancy etc. [10]. Prevalence of dyspnea is gradually increasing due to environmental pollution, industrialization, smoking pattern, and post-COVID pulmonary fibrosis following recent COVID-19 pandemic. Its presentation varies from acute, acute on chronic and chronic dyspnea. Approach also varies depending on presentation, causes and severity. The primary treatment of shortness of breath is directed at its underlying cause [11]. Extra supplemental oxygen is effective in those with hypoxia; however, this has no effect in those with normal blood oxygen saturations [9, 12].